Planktic foraminiferal diversity: Logistic growth overprinted by a varying environment (2016)
This study statistically assesses the relationship between the planktic foraminiferal long-term diversity pattern (~170 Ma to Recent) and four major paleobiological diversification models: (i) the ‘Red Queen’ (Van Valen, 1973; Raup et al., 1973), (ii) the turnover-pulse (Vrba, 1985; Brett and Baird, 1995), (iii) the diversity-equilibrium (Sepkoski, 1978; Rosenzweig, 1995), and (iv) the ‘complicated logistic growth’ (Alroy, 2010a). Our results suggest that the long-term standing diversity pattern and the interplay between origination and extinction rates displayed by this group do not correspond to the first three models, but can be more readily explained by the fourth scenario. Consequently, these patterns are likely controlled by a combination of planktic foraminiferal interspecific competition as well as various environmental changes such as marine global temperatures that could impacted the niches within the upper mixed layer within the oceans. Moreover, as other global long-term patterns have been interpreted as reflecting ‘complicated logistic growth’, this study further suggests that the interplay between abiotic and biotic factors are fundamental elements influencing the evolutionary processes over the extensive history of the biota. © 2016 Author(s).